Evaluating the Implementation of Early Childhood Education Curriculum in Vietnam: Perspectives from Teachers and Parents - Cham Is Na Uy (DZURRIYAT : Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Early childhood education (ECE) in Vietnam has experienced substantial reforms over the past decades, shifting from traditional teacher-centered practices to competency-based, child-centered approaches designed to promote holistic development. This study aims to evaluate the implementation of Vietnam’s early childhood curriculum from the perspectives of teachers and parents. Using a systematic literature review approach, empirical and theoretical studies published between 2010 and 2025. The findings reveal significant gaps between policy intentions and practical realities. Teachers reported limited resources, insufficient professional training, and cultural constraints rooted in Confucian traditions, while parental involvement remained low due to limited awareness and diverse family dynamics. At the systemic level, disparities in infrastructure, funding, and policy coherence continue to hinder equitable curriculum implementation across regions. These findings emphasize the need for enhanced teacher capacity-building, culturally responsive school–parent partnerships, and context-sensitive policy strategies to improve curriculum fidelity and educational quality